KURIKULUM MERDEKA DAN BUDAYA HIDUP BERSIH DI MTS SAFINDA SURABAYA - Subhan, Moh (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
This research discusses the culture of clean and healthy living in Tsanawiyah madrasahs, in order to shape students to have a religious character. This research method is descriptive qualitative, the data collection techniques used are interviews, documentation and observation. The results of this research make students implement a clean and healthy culture. by teaching noble values of personality that are cultivated in order to achieve optimal results, in accordance with Islamic teachings, namely the values of Islamic education through cleanliness and education that applies the principles of the free curriculum so that it becomes a culture of behavior in the life of a pluralistic society through cultural policies with guidance religious values, also by emphasizing acceptance of reality for religious, pluralistic and multicultural followers so that they can be applied in the life of a pluralistic society.